Symbolic representations and cardinal knowledge in 3- and 4-year-old children - Rodríguez Cesarini, Jimena Soledad (2018)
This study analyzes the impact of iconic representations of quantity (objects and images) and arbitrary representations (spoken number words) on the performance of 3-, 3.5- and 4-year-old children when building collections of 1?6 items. We used an adaptation of the Give-N task in which children had to use the information about quantity transmitted by collections of bottle caps, round dots on cards and number words. The results show that iconic representations helped children produce sets which cardinal values were larger than their known number words. This pattern of results was found in a transitional stage to learning that a given number word picks out an exact cardinal value, for set sizes 3 and 4 among children in all three age groups. These findings suggest that children would be in different (but proximal) levels of cardinal competency according to the symbolic modality employed to present the quantitative information.